PERSETERUAN MONARKI DALAM NASKAH DRAMA LA TINRO KARYA ROSTAN YUNIARDI (KAJIAN SOSIOLOGI SASTRA IAN WATT) - Ardiansyah, Ardiansyah; Nensilianti, Nensilianti; Tuflih, Muhammad Alfian (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the monarchical feud in the stageplay script La Tinro by Rostan Yuniardi by using the study of  the sociology of literature by Ian Watt. This research type is descriptive qualitatives. Researcher found, the identity or background of the author in terms of social status and ethnic origin affect the selectionof plots and characterizations of the drama script. The reflection of people’s lives is dominated by the description of the position and responsibilities of a leader and differences in social strata. Monarchy feuds in the text tell of the position of a king who is very vulnerable by personal interests even from those closest to him.